Anthropology, Art, and Folklore: Competing Visions of Museum Collecting in Early Twentieth-Century America. Issue 1 (1st July 2019) - Jacknis, Ira
Abstract : In the great age of museum institutionalization between 1875 and 1925, museums competed to form collections in newly defined object categories. Yet museums were uncertain about what to collect, as the boundaries between art and anthropology and between art and craft were fluid and contested. As a case study, this article traces the tortured fate of a large collection of folk pottery assembled by New York art patron Emily de Forest (1851–1942). After assembling her private collection, Mrs. de Forest encountered difficulties in donating it to the American Museum of Natural History and the Metropolitan Museum of Art. After becoming part of the Philadelphia Museum of Art, it finally found a home at the Pennsylvania State Museum of Anthropology. Emily de Forest represents an initial movement in the estheticization of ethnic and folk crafts, an appropriation that has since led to the establishment of specifically defined museums of folk art and craft.